An analysis of factors and conditions pertaining to the rise of the sharing economy. Issue 3 (6th April 2021) - Yeganeh, Hamid
Abstract : Purpose: This study aims to examine the various factors and conditions pertaining to the rise of the sharing economy. Design/methodology/approach: After framing the sharing economy concept, the study adopts a multidisciplinary approach and relies on the extant literature to analyze and classify eight major groups of factors behind the rise of the sharing economy. Findings: The analysis indicates that the sharing economy (1) represents a significant paradigm shift emphasizing utilization rather than possession and relying on mutual trust, collaboration and reciprocity; (2) benefits from fundamental transformations such as the world population growth, global urbanization, surge in the world middle class and the convergence of tastes and preferences; (3) relies on technological innovation but is affected by socio-cultural and psychological conditions; (4) is driven by emerging trends in consumption, marketing and working conditions; (5) benefits from lax or nonexistent regulation and taxation; and (6) is recognized as clean and environmentally friendly. Originality/value: This paper's chief contribution resides in adopting a multidisciplinary perspective to offer an in-depth analysis of the various types of factors behind the rise of the sharing economy.